2016
DOI: 10.12659/msm.897146
|View full text |Cite
|
Sign up to set email alerts
|

Dose Evaluation of Fractionated Schema and Distance From Tumor to Spinal Cord for Spinal SBRT with Simultaneous Integrated Boost: A Preliminary Study

Abstract: BackgroundThis study investigated and quantified the dosimetric impact of the distance from the tumor to the spinal cord and fractionation schemes for patients who received stereotactic body radiation therapy (SBRT) and hypofractionated simultaneous integrated boost (HF-SIB).Material/MethodsSix modified planning target volumes (PTVs) for 5 patients with spinal metastases were created by artificial uniform extension in the region of PTV adjacent spinal cord with a specified minimum tumor to cord distance (0–5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This concept has led to research for an SIB that shapes the dose to the local control of the tumor with significant dose reductions at the spinal cord (Table 3). 20,28,29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept has led to research for an SIB that shapes the dose to the local control of the tumor with significant dose reductions at the spinal cord (Table 3). 20,28,29…”
Section: Discussionmentioning
confidence: 99%
“…This concept has led to research for an SIB that shapes the dose to the local control of the tumor with significant dose reductions at the spinal cord (Table 3). 20,28,29 Several studies suggested that SBRT provides 70% to 100% rate of 1-year local control across clinical scenarios. 17,[30][31][32] When performed as the primary treatment modality, SBRT is associated with long-term local control rate of 80% to 95% for patients with spinal metastases.…”
Section: Discussionmentioning
confidence: 99%